MANAJEMEN PENDIDIKAN ISLAM - Barsihannor B (Management of Education: Jurnal Manajemen Pendidikan Islam, 2021)
This article examines thoughts of Prof. Dr. Mujamil Qomar, M.Ag. which expressly states that the success of Islamic education in the level of realityexpectations one of which is determined by the management of Islamic education that serves the task of advancing the implementation, implementation or application of Islamic education institutionally. Among Qomar's thoughts on the management of Islamic education that is pithy and deserves an in-depth study is the nature of Islamic education management and its implications, philosophical objects and praxis as well as the dimensions of Islamic education management, the characteristics and characteristics of Islamic education management, the difference between Islamic education management and education management , as well as about the existence and constraints of Islamic education management. Thought Qomar can be explored clearly in three works, namely Manajemen Pendidikan Islam: Strategi Baru Pengelolaan Lembaga Pendidikan Islam (Management of Islamic Education: New Strategy Management of Islamic Education Institutions), Dimensions of Management of Islamic Education, and Strategy of Islamic Education, as well as other works that are not directly related to the discussion of Islamic education management.